2012
DOI: 10.1016/j.imlet.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Complementing antibody profiles: Assessing antibody function on antigen microarrays

Abstract: Antibody effector functions other than neutralization depend on interactions with soluble and cellular components of the immune system. Antigen recognition is usually oligoclonal, with the different clones of antibodies belonging to different classes, subclasses, glycoforms and having different affinities and epitope specificities. Thus, composition of immune complexes determines biological effects mainly via interactions with FcR and complement proteins. Antibodies are capable of triggering any of the three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In an attempt to simultaneously monitor antibody and complement binding to various autoantigens, we have developed a functional immunomics approach 4 , 5 allowing a complex analysis of serological events in SLE. Interestingly, we observed that copious amounts of complement products are fixed by nucleic acids but not other negatively charged molecules in SLE patients with decreased complement C4 levels 6 (and manuscript in preparation), which finally led us to formulate the hypothesis presented below.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to simultaneously monitor antibody and complement binding to various autoantigens, we have developed a functional immunomics approach 4 , 5 allowing a complex analysis of serological events in SLE. Interestingly, we observed that copious amounts of complement products are fixed by nucleic acids but not other negatively charged molecules in SLE patients with decreased complement C4 levels 6 (and manuscript in preparation), which finally led us to formulate the hypothesis presented below.…”
Section: Introductionmentioning
confidence: 99%
“…When antigens are arrayed, a binding pattern called antibody profile, characteristic of the tested serum, is generated [1], [2]. This pattern is usually revealed by secondary antibodies labeled suitably to allow qualitative and quantitative detection of the bound serum antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this simplicity is the convergence of antibody effector functions: no matter which antibody isotype, what affinity and concentration, what glycoform initiates the response, the effector function can be essentially the same. Our group has developed two approaches to measure antibody function in an antigen specific manner: complement fixation (Papp et al 2007 , 2012a ; Prechl et al 2012 ) and cell activation (Szittner et al 2013 ). Both of these platforms utilized protein microarray technology, with antigens being printed as arrays of microspots on a solid surface (Prechl et al 2010 ; Herbáth et al 2014 ).…”
Section: Quantitation Of Biological Effectsmentioning
confidence: 99%